2020
DOI: 10.4186/ej.2020.24.4.19
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis Kinetic Analysis of Biomasses: Sugarcane Residue, Corn Cob, Napier Grass and their Mixture

Abstract: The aim of this study is to investigate pyrolysis kinetic parameters of three high potential energy biomasses including sugarcane residue (tops and leaves), corn cob and Napier grass via thermogravimetry analysis (TGA). In addition, those of their mixture at 1:1:1 by mass is explored. Activation energy and pre-exponential factor were the two considered parameters calculated by following the Ozawa-Flynn-Wall method using condition of 30-900C with heating rates of 5, 10, 20 and 40C/min. The derivative thermogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 45 publications
(68 reference statements)
0
1
0
Order By: Relevance
“…Besides that, Braga, Melo et al 43 evaluated Napier grass activation energy ranges from 193 to 280 kJ/mol for pyrolysis. Lastly, Phuakpunk, Chalermsinsuwan et al 44 obtained a large range of activation energy which ranges from 87.8 to 887.2 kJ/mol. So, it can be concluded that those values obtained in this study are in good agreement with literature.…”
Section: Resultsmentioning
confidence: 99%
“…Besides that, Braga, Melo et al 43 evaluated Napier grass activation energy ranges from 193 to 280 kJ/mol for pyrolysis. Lastly, Phuakpunk, Chalermsinsuwan et al 44 obtained a large range of activation energy which ranges from 87.8 to 887.2 kJ/mol. So, it can be concluded that those values obtained in this study are in good agreement with literature.…”
Section: Resultsmentioning
confidence: 99%